2017
DOI: 10.5194/gmd-10-2567-2017
|View full text |Cite
|
Sign up to set email alerts
|

The carbon cycle in the Australian Community Climate and Earth System Simulator (ACCESS-ESM1) – Part 1: Model description and pre-industrial simulation

Abstract: Abstract. Earth system models (ESMs) that incorporate carbon-climate feedbacks represent the present state of the art in climate modelling. Here, we describe the Australian Community Climate and Earth System Simulator (ACCESS)-ESM1, which comprises atmosphere (UM7.3), land (CABLE), ocean (MOM4p1), and sea-ice (CICE4.1) components with OASIS-MCT coupling, to which ocean and land carbon modules have been added. The land carbon model (as part of CABLE) can optionally include both nitrogen and phosphorous limitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 59 publications
2
74
0
Order By: Relevance
“…1). Law et al (2017) also showed that the climate simulations of the three model versions are very similar.…”
Section: Model Configurationmentioning
confidence: 69%
See 4 more Smart Citations
“…1). Law et al (2017) also showed that the climate simulations of the three model versions are very similar.…”
Section: Model Configurationmentioning
confidence: 69%
“…A selection of CMIP5 simulations have now been performed with the ESM version of AC-CESS, ACCESS-ESM1 (Law et al, 2017). Here, we present the performance of the land and ocean carbon cycle components of ACCESS-ESM1 over the historical period .…”
Section: T Ziehn Et Al: Access-esm1 Historical Simulationsmentioning
confidence: 99%
See 3 more Smart Citations